Modifiable risk factors associated with bronchiolitis. (October 2017) - Nenna, Raffaella; Cutrera, Renato; Frassanito, Antonella; Alessandroni, Claudia; Nicolai, Ambra; Cangiano, Giulia; Petrarca, Laura; Arima, Serena; Caggiano, Serena; Ullmann, Nicola; Papoff, Paola; Bonci, Enea; et al.
Background: We sought to clarify possibly modifiable risk factors related to pollution responsible for acute bronchiolitis in hospitalized infants. Methods: For this observational study, we recruited 213 consecutive infants with bronchiolitis (cases: median age: 2 months; age range: 0.5–12 months; boys: 55.4%) and 213 children aged <3 years (controls: median age: 12 months; age range: 0.5–36 months; boys: 54.5%) with a negative medical history for lower respiratory tract diseases hospitalized at 'Sapienza' University Rome and IRCCS Bambino Gesù Hospital. Infants' parents completed a standardized 53-item questionnaire seeking information on social-demographic and clinical characteristics, indoor pollution, eating habits and outdoor air pollution. Multivariate logistic regression analyses were run to assess the independent effect of risk factors, accounting for confounders and effect modifiers. Results: In the 213 hospitalized infants the questionnaire identified the following risk factors for acute bronchiolitis: breastfeeding ⩾3 months (OR: 2.1, 95% confidence interval [CI]: 1.2–3.6), presence of older siblings (OR: 2.8, 95% CI: 1.7–4.7), ⩾4 cohabitants (OR: 1.5, 95% CI: 1.1–2.1), and using seed oil for cooking (OR: 1.7, 95% CI: 1.2–2.6). Having renovated their home in the past 12 months and concurrently being exposed daily to smoking, involving more than 11 cigarettes and two or more smoking cohabitants, were more frequent factors in cases than in controls ( p = 0.021 and 0.05), whereas self-estimated proximity to road and traffic was similar in the two groups. Conclusions: We identified several risk factors for acute bronchiolitis related to indoor and outdoor pollution, including inhaling cooking oil fumes. Having this information would help public health authorities draw up effective preventive measures – for example, teach mothers to avoid handling their child when they have a cold and eliminate exposure to second-hand tobacco smoke.